2020
DOI: 10.17072/1994-9952-2020-1-48-53
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Composition of Agricultural Maple (Acer Platanoides L.) in the Urban Environment

Abstract: The results of studies of the characteristics of the biochemical composition of acutifolia in the conditions of a large industrial center of Naberezhnye Chelny (Republic of Tatarstan) are presented. Under condi-tions of intense technogenic load, the maple has a higher ascorbate oxidase activity at the initial stages of active vegetation and lower at the end of the vegetation. The content of ascorbic acid decreases during the growing season in man-made stands. Under conditions of a high content of pollutants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The content of non-enzymatic components of the antioxidant system in leaves when treated with innovative forms of fertilizers, (M±m). It is known that the content of AA in the leaves is a manifestation of non-enzymatic components of the antioxidant system [23], moreover, under stress conditions, a decrease in AA occurs [24]. Also, we found that when processing innovative forms of fertilizers in tea leaves, an active significant (LSD (p ≤0.05)=10) occurs.2) ascorbic acid growth (table 1).…”
Section: Resultssupporting
confidence: 52%
“…The content of non-enzymatic components of the antioxidant system in leaves when treated with innovative forms of fertilizers, (M±m). It is known that the content of AA in the leaves is a manifestation of non-enzymatic components of the antioxidant system [23], moreover, under stress conditions, a decrease in AA occurs [24]. Also, we found that when processing innovative forms of fertilizers in tea leaves, an active significant (LSD (p ≤0.05)=10) occurs.2) ascorbic acid growth (table 1).…”
Section: Resultssupporting
confidence: 52%